"I'm really worried for my teaching spirit": professional agency, curriculum change and the primary arts specialist teacher. Issue 4 (3rd July 2020) - Chapman, Sian; Wright, Peter; Pascoe, Robin
ABSTRACT: Arts specialist teachers have a unique place in primary schools. They are often the sole teacher responsible for an entire learning area and hence commonly provide leadership and drive the curriculum implementation of the arts in and for their school. This responsibility finds us asking questions about the ability of arts specialist teachers to create professional agency in an increasingly challenging school environment. Using a narrative portraiture approach, and seven propositions for professional agency, we focus on a single teacher in order to consider how both individual and structural elements are understood from the perspective of an arts specialist. Conditions explored include relationships, time, purpose and constraints, work-related identity, experiences, and work communities. Challenges such as isolation, ongoing support and the development of community are highlighted as potential difficulties in the process of developing agency. The study contributes to an understanding of the personal cost and potential growth the development of professional agency provides.